(untitled) (ҚазҰУ хабаршысы. Экономика сериясы, 2017)
The formation of a fundamentally different model of interaction between government and business entities in the field of taxation has determined the necessity for consideration of the tax component in the total economic strategy of the enterprises. In this regard there is a need in the formation of individual tax policies of business entities, covering issues of optimization of tax burden. However, despite the particular relevance of the research question the effect of the value of the tax burden on business entities, this issue found its solution only in the form of general conclusions, calling for increased activity in the reform of the tax system. At the same time despite the fact that in many works of domestic authors there is the mention of the term “tax burden of the business entity”, its content is not disclosed in full. Moreover, authors of numerous publications on tax issues, not made a comprehensive assessment of the enterprises response to the dynamics of the ratio of the tax burden. But, along with other factors that affect the process of formation of a tax policy of the enterprise, the amount of the tax burden plays a significant role in the adoption of the economic entity solutions in the field of taxation. Thus, a need arises to research a range of outstanding issues related to the management of economic entities in the sphere of tax relations.